Use of the intraoral microblaster for placement of pit and fissure sealants: Clinical case. - Saravia-Rojas, Miguel Ángel (2022)
Pit and fissure sealants have proven to be an efficient and effective alternative to protect occlusal surfaces from the development of carious lesions. A review of the abrasive air used in restorative dentistry is carried out and a clinical case of the use of this technology for the placement of pit and fissure sealants is presented.